Impact of the Higher Education Training on the Labor Market Demand : Evidence from African Higher Education - Ralainirina Razokiny Eric; Jean Tsitaire Arrive; Ralaivao Hanginiaina Emynorane (International Journal of Educational Research, 2025)
This study aims to analyze the impact of higher education training on labor market demand in Africa, using a documentation study approach. In an ever-evolving global context, higher education plays an important role in preparing individuals to face the demands of a dynamic labor market. However, in many African countries, there is a gap between the skills provided by higher education institutions and the needs of the labor market. Through documentation studies, this study collects and analyzes secondary data originating from various government reports, international institutions, and previous studies regarding the relationship between higher education and labor demand in Africa. The findings show that although higher education in Africa can improve the quality of human capital, there is a mismatch between the skills taught and the skills required by the industrial sector. This study also identified key challenges, such as a lack of relevant curriculum and limited educational facilities, that impact the effectiveness of training in meeting labor market needs. Therefore, this study recommends curriculum reform that is more adaptive to industry needs and increased collaboration between educational institutions and the private sector to create more relevant and quality training programs